Pengaruh Pengenalan Lapangan Persekolahan dan Persepsi Kesejahteraan Guru Terhadap Minat Menjadi Guru Mahasiswa Prodi Pendidikan Administrasi Perkantoran FKIP UNS Angkatan 2020 - Nur Chotimah Wiji Utami; Tutik Susilowati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research aims to (1) determine whether there is an influence of PLP on interest in becoming a teacher for students of the 2020 FKIP UNS Office Administration Education Study Program, (2) determine whether or not there is an influence of teacher welfare perceptions on interest in becoming a teacher for students of the 2020 FKIP UNS Office Administration Education Study Program, (3) determine whether or not there is an influence of PLP and perceptions of teacher welfare on the interest in becoming a teacher for students of the Office Administration Education Study Program FKIP UNS class of 2020. This research is a quantitative research with the population used in this research being students of the Office Administration Education Study Program Class of 2020 who have already carried out PLP. The sample used a saturated sampling technique, which means that the entire population was used as a research sample of 75 students. Data collection was carried out by distributing research questionnaires. The data analysis technique uses multiple linear regression methods with the help of IBM SPSS version 25 software. The results of the research show that: (1) there is a positive and significant influence of Introduction to the School Field (PLP) on interest in becoming a teacher for students of the 2020 FKIP UNS Office Administration Education Study Program. proven by the value of tcount (2.04) > ttable (1.99) and a significance value of 0.04 < 0.05, (2) there is a positive and significant influence on the perception of teacher welfare on interest in becoming a student teacher at the Office Administration Education Study Program, FKIP UNS class of 2020 is proven by the value of tcount (5.06) > ttable (1.99) and a significance value of 0.00 < 0.05, (3) there is a positive and significant influence together with the introduction of the school field and the perception of teacher welfare on interest. being a student teacher of the 2020 FKIP UNS Office Administration Education Study Program is proven by the value of Fcount (62.82) > Ftable (3.97). The results of this research show that the effective contribution value together is 0.63 or 63%, while the remaining 37% is influenced by other factors or variables not examined in this research.